Pengaruh Kompensasi Finansial dan Kecerdasan Emosional terhadap Kinerja Pegawai Dinas Sosial Kabupaten Bantul - Latif Nur Azmi, Muhammad; Fitri Wahyuningtyas, Yunita (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
There are indications of a decrease in the performance of employees of the Bantul Regency Social Office, which is caused by several factors. This study aims to determine the effect of financial compensation and emotional intelligence on the performance of Bantul Regency Social Service Employees. This research is a quantitative research using SPSS data processing software version 25. The population in this study was all employees of the Bantul Regency Social Office which amounted to 114 people. Eighty-nine respondents became a sample determined using Solvin's formula. Samples were collected using simple random sampling, a non-probability sampling approach, with samples drawn randomly from the population. The findings of this study suggest that financial compensation does not significantly affect performance, whereas emotional intelligence affects performance positively and significantly and Financial compensation and emotional intelligence affect performance significantly and positively together.